2019
DOI: 10.3390/vetsci6030072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Undenatured Type II Collagen (UC-II) as Compared to Robenacoxib on the Mobility Impairment Induced by Osteoarthritis in Dogs

Abstract: Osteoarthritis (OA) is a chronic disease that requires a multimodal therapeutic approach. The aim of this study was to evaluate the effects of undenatured type II collagen (UC-II) as compared to robenacoxib in dogs affected by OA. Our hypothesis was that the two compounds would be similar (non-inferiority) in improving mobility. To test this hypothesis, a complete orthopedic examination, x-ray and the Liverpool Osteoarthritis in Dogs (LOAD) survey were performed in dogs affected by OA before and after the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
2
24
0
1
Order By: Relevance
“…In the present study, UC-II supplementation improved gait stability, as previously reported (23). The reduction of the claudication severity observed with UC-II supplementation in dogs proves these results (24). The chondrocyte cell death leads to cartilage deterioration, joint space narrowing, subchondral bone sclerosis, the formation of bone osteophytes (bony outgrowths), and eventually deformity of bone ends (25).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, UC-II supplementation improved gait stability, as previously reported (23). The reduction of the claudication severity observed with UC-II supplementation in dogs proves these results (24). The chondrocyte cell death leads to cartilage deterioration, joint space narrowing, subchondral bone sclerosis, the formation of bone osteophytes (bony outgrowths), and eventually deformity of bone ends (25).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, UC-II supplementation improved gait stability, as previously reported ( 23 ). The reduction of the claudication severity observed with UC-II supplementation in dogs proves these results ( 24 ).…”
Section: Discussionmentioning
confidence: 57%
“…Another water-soluble UC-II form also exhibited similar noteworthy efficiency in relieving pain and inflammation in collagen-induced arthritis in mice, as well as moderately arthritic dogs after 150 days of supplementation with 10 mg of dosage when compared to control dogs [98,99]. In a clinical, randomized, controlled, and prospective study [79], 60 client-owned dogs were randomly allocated to the R group (n = 30, robenacoxib 1 mg/kg/day) and the UC-II group (UC-II 1 tablet (40 mg)/day) for a 30 days study. Based on the data obtained from the study, there was a significant reduction in the Liverpool osteoarthritis in dogs (LOAD) and mobility scores among T0 and T30 of similar size between the two groups (R = 31.5%, UC-II = 32.7%).…”
Section: Uc-ii Usage In Dogsmentioning
confidence: 98%
“…Previous experiments have evaluated the efficacy of undenatured type II collagen in known arthritic dogs ( Deparle et al, 2005 ) and in dogs with temporary mobility impairment ( Stabile et al, 2019 ). In order to evaluate the efficacy and safety of undenatured type II collagen in healthy Labrador Retrievers, this experiment used an endurance exercise model to induce inflammation and cartilage turnover.…”
Section: Introductionmentioning
confidence: 99%